Synthesis and Characterization of New Photoluminescent Oxadiazole/Carbazole-Containing Polymers - Simona Concilio; Valeria Bugatti; Pio Iannelli; Stefano Piotto Piotto (International Journal of Polymer Science)
We report on the synthesis and the characterization of a new class of segmented polyethers POC containing the oxadiazole and carbazole units. The polymers exhibit a high thermal stability, high glass transition temperatures, and good solubility in common organic solvents, despite the extended aromatic portion in the main polymer chain. The synthetic procedures are simple, and no acid side-products are obtained. According to previous reports on oxadiazole/carbazole-containing materials, POCs show high photoluminescence activity in the blue region of the visible spectra. The good solubility in chlorinate solvents allows the preparation of films with homogeneous thickness by spin coating. Glass transition temperature in the range 115–125∘C ensures good stability of film morphology at room temperature. The only exception is POC(6), which shows a poor solubility and higher 𝑇𝑔 (170∘C), due to its shorter aliphatic chain portion. For these features, polymers POC are potential candidate materials for fabricating blue light-emitting devices.